Isoflavones Effects on Vascular and Endothelial Outcomes: How Is the Gut Microbiota Involved? - Samuele Laudani; Justyna Godos; Giovanni Luca Romano; Lucia Gozzo; Federica Martina Di Domenico; Irma Dominguez Azpíroz; Raquel Martínez Diaz; Francesca Giampieri; José L. Quiles; Maurizio Battino; Filippo Drago; Fabio Galvano; et al. (MDPI AG, 2024)
Isoflavones are a group of (poly)phenols, also defined as phytoestrogens, with chemical structures comparable with estrogen, that exert weak estrogenic effects. These phytochemical compounds have been targeted for their proven antioxidant and protective effects. Recognizing the increasing prevalence of cardiovascular diseases (CVD), there is a growing interest in understanding the potential cardiovascular benefits associated with these phytochemical compounds. Gut microbiota may play a key role in mediating the effects of isoflavones on vascular and endothelial functions, as it is directly implicated in isoflavones metabolism. The findings from randomized clinical trials indicate that isoflavone supplementation may exert putative effects on vascular biomarkers among healthy individuals, but not among patients affected by cardiometabolic disorders. These results might be explained by the enzymatic transformation to which isoflavones are subjected by the gut microbiota, suggesting that a diverse composition of the microbiota may determine the diverse bioavailability of these compounds. Specifically, the conversion of isoflavones in equol-a microbiota-derived metabolite-seems to differ between individuals. Further studies are needed to clarify the intricate molecular mechanisms behind these contrasting results.